Leadership trends in institutions of Higher Education: A bibliometric review - Suárez-Amaya, Wendolin; Ganga-Contreras, Francisco; Alarcón-Henríquez, Nancy; Abello-Romero, Juan (Revista de Ciencias Sociales, 2024)
This Investigation aims to analyze scientific production and thematic trends in the field of leadership in institutions of higher education. This is a documentary type review which seeks to shows how a bibliometric analysis of the Web of Science database is conducted. Information processing was carried out using the Biblioshiny and VOSviewer tools. The criterias for the searches and analysis were: The evolution in publications by areas of knowledge, countries, affiliations, authors and their collaborations, relevant journals and articles, as well as topics, with emphasis on the areas of education and management. The results suggest a considerable increase, 120% between 2017 and 2018, with an impact on related areas such as psychology and sustainability. Production is concentrated in the United States and England, however, when it comes to authors, attention needs to be paid to groups from the United Kingdom, China and Norway. In terms of themes, competencies, soft skills and well-being stand out. It is concluded that scientific production on leadership in higher education is expanding, which represents a research niche with development possibilities, whose interests in recent times have leaned towards practices necessary to guarantee success when exercising leadership.